PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF UNTUK MATERI LUAS DAERAH DAN VOLUME BENDA PUTAR SMA/MA - Niadika Ayu Putri; Armis Armis; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to develop a valid computer based learning media to help students to understand the topic of area and volume of revolution. This research uses development model by Sugiyono, the following stages are: (1) potential and problem; (2) collect information; (3) product design; (4) design validation; (5) design revision; (6) product testing; (7) product revision; (8) usage testing; and (9) product revision. At the stage of potential and problem, the researcher created a needs analysis of observation and interviews with Mathematics teacher. Then, researcher collected the informations by conducting literature studies. Product design is through two stages, that are making paper based design and then computer based that used microsoft power point program. The learning media is validated by three validators used validation sheet and obtained an average score of 3,76 (very valid). Then revised based on the input from validators. The revised learning media was tested by questionnaire technique using student response questionnaire. The testing was conducted through two stages towards the students of class XI MIPA 2 SMA N Binaan Khusus Dumai. The first stage is a product testing of 6 students. Further revision of the product according to the student's suggestion on product testing. The second stage is the usage testing of 25 students and obtained an average score of 3.58 (very practice). Then revised the product according to the student's suggestion on usage testing. Thus, can be concluded that computer based learning media is valid and qualified practicalities.Key Words: Computer Based Learning Media, Development, Area and Volume of Revolution